Development of ISTP (Indonesian Student Test Platform) evaluation tool to analyze student competency - Irbah Khairunnisa; Dewie Tri Wijayanti; Tri Sudarwanto (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2020)
ISTP is a website platform designed and developed to provide evaluation services and quiz online. Through the program site, teachers and students are expected to adapt to the test method switching and value recapitulation from the Manual (offline) method to the digital (online) method. This website can be used easily by both teachers and learners. The purpose of this research is to obtain a description of 1) product development in the form of Evaluation of ISTP, 2) Feasibility evaluation tool (Indonesian Student Test Platform) through the process of study and validation Experts, 3) The response of learners as a user to the assessment tool of ISTP that has been tested. The reseach development applied thiagarajan’s 4-D model. It is start from the definition stage to the development stage. The study is test on the 24 students at SMA Negeri 1 Giri. The research instruments were the questionnaire of material review and media, the material and media validity sheet, and the questionnaire of students’ responses. The result of study suggest that the ISTP is very feasible. Therefore, it can be concluded that the ISTP is effectively applied as an alternative evaluation tool in SMA Negeri 1 Giri.